The Reader, the Writer, and the Book in How to Make Love to a Negro Without Getting Tired by Dany Laferrière - Galmiche-Essue, Julia (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2023)
Many critics have studied the relationship that unfolds between black men and white women in the novel How to Make Love to a Negro Without Getting Tired (1985) by Haitian-born Quebecois author Dany Laferrière. However, another type of relationship in Laferrière’s work seems just as important, if not more important: the relationship between the aspiring writer and female readers as mediated by the book. This new angle allows for a rereading of the novel around a central axis—the idea of the literary Other, and the way it is articulated in the novel through the fictionalized book. This article first examines how, at the diegetic level, women own books, which makes them desirable to the narrator; in contrast, at the metadiegetic level, the terms of this equation are reversed, for it is now books, as mediators, which make objectified women attractive by being possessed by them. The relationship between the male reader (subject), the book (mediator), and the female reader (object) is then replaced by the relationship between the female reader (subject), the book (mediator), and the male reader (object), as the English-speaking white woman undertakes to judge the French-speaking Black (novelist) on the basis of books. In this context, the black male reader has no choice but to analyze the white female reader using her own book-based preconceptions. Indeed, whereas the white female reader judges the human subject based on his relationship to the book as an object, the black male reader uses the book to understand said human subject. It is therefore up to the aspiring black writer to help the white female reader rethink her relationship with books in general, and with literature in particular. This article shows that the narrator’s objective (as a writer) is ultimately for his book to be read—in other words, to be possessed—by women, as he himself possesses women (as a womanizer).